2019
DOI: 10.15252/embr.201846888
|View full text |Cite
|
Sign up to set email alerts
|

A micro RNA switch controls dietary restriction‐induced longevity through Wnt signaling

Abstract: Dietary restriction (DR) is known to have a potent and conserved longevity effect, yet its underlying molecular mechanisms remain elusive. DR modulates signaling pathways in response to nutrient status, a process that also regulates animal development. Here, we show that the suppression of Wnt signaling, a key pathway controlling development, is required for DR‐induced longevity in Caenorhabditis elegans. We find that DR induces the expression of mir‐235, which inhibits cwn‐1/WNT4 expression by binding to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 66 publications
3
23
0
Order By: Relevance
“…When pry-1 was knocked down in mom-2(or42) and cwn-2(ok895) backgrounds, life span extension was significantly reduced in mom-2 mutants (13.6% reduction in mean life span, p < 0.05, Figure 3 A; Table S2 ) but remained unchanged in the cwn-2 animals ( Figure 3 B; Table S2 ). We also analyzed the requirements of bar-1 / β-catenin , a component of the canonical WNT signaling that plays a role in aging ( Xu et al., 2019 ; Zhang et al., 2018 ), in the mom-2 - pry-1 pathway. Since pry-1 -mediated WNT signaling negatively regulates bar-1 , removing bar-1 function is expected to suppress the phenotype of pry-1 mutants.…”
Section: Resultsmentioning
confidence: 99%
“…When pry-1 was knocked down in mom-2(or42) and cwn-2(ok895) backgrounds, life span extension was significantly reduced in mom-2 mutants (13.6% reduction in mean life span, p < 0.05, Figure 3 A; Table S2 ) but remained unchanged in the cwn-2 animals ( Figure 3 B; Table S2 ). We also analyzed the requirements of bar-1 / β-catenin , a component of the canonical WNT signaling that plays a role in aging ( Xu et al., 2019 ; Zhang et al., 2018 ), in the mom-2 - pry-1 pathway. Since pry-1 -mediated WNT signaling negatively regulates bar-1 , removing bar-1 function is expected to suppress the phenotype of pry-1 mutants.…”
Section: Resultsmentioning
confidence: 99%
“…No defects in dauer arrest or development have been reported for these miRNAs, however cel - mir - 235 is required for maintaining L1 arrest, when eggs hatch in the absence of food 12 , while dietary restriction of C . elegans adult worms induces expression of mir - 235 31 , mir - 228 and mir - 71 32 .…”
Section: Resultsmentioning
confidence: 99%
“…In C. elegans, miRNAs have been shown to participate in the regulation of metabolic processes, cell development and lifespan determination 31,32 . Increasing evidence suggests that some miRNAs play critical roles in response to the toxicity of nanomaterials 20,30 .…”
Section: Discussionmentioning
confidence: 99%
“…mir-235, a sole orthologue of mammalian miR-92 in oncogenic miR-17-92 cluster, acts in the hypodermis and glial cells to arrest postembryonic developmental events in neuroblasts and mesoblasts 31 . mir-235 is induced by dietary restriction at the end of larval development, which subsequently suppresses Wnt signaling by inhibiting cwn-1/WNT4 and thereby promotes longevity 32 . Our previous study found that mir-235(n4504) mutants display a sensitive property to GO toxicity 30 .…”
mentioning
confidence: 99%